2023
DOI: 10.1002/ps.7702
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of nine insecticides on Drosophila suzukii and its major pupal parasitoid Trichopria drosophilae

Fabrizio Lisi,
Ramzi Mansour,
Carmelo Cavallaro
et al.

Abstract: BackgroundAlthough the pupal parasitoid Trichopria drosophilae is employed in conservative and augmentative biocontrol of Drosophila suzukii infestations, current pest management strategies mostly rely on multiple insecticide applications. In this context, the aim of the study was to investigate the baseline toxicity of nine insecticides on D. suzukii larvae and their multiple sublethal effects (LC10) on immature stages of the pest feeding on contaminated diet and T. drosophilae developing within the intoxicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…For two pupal parasitoids of D. suzukii, the sensitivity to dry residues of eight commercial insecticides was higher for P. vindemmiae than for T. anastrephae, resulting in a signi cant reduction in parasitism for the former species (Schlesener et al 2019). Sublethal doses of Cyazypyr and dimethoate negatively affected the success of parasitism and the number of progeny of T. drosophilae (Lisi et al 2023). The results of our study were consistent with those of these previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For two pupal parasitoids of D. suzukii, the sensitivity to dry residues of eight commercial insecticides was higher for P. vindemmiae than for T. anastrephae, resulting in a signi cant reduction in parasitism for the former species (Schlesener et al 2019). Sublethal doses of Cyazypyr and dimethoate negatively affected the success of parasitism and the number of progeny of T. drosophilae (Lisi et al 2023). The results of our study were consistent with those of these previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the increased mortality caused by indirect contact with drugs, the long-term, trans-generation effects of sublethal doses of pesticides on parasitic wasps should also be considered when assessing the safety of pesticides (Costa et al 2014;Lisi et al 2023). Treating host larvae or pupae with insecticides can affect the parasitic behavior of parasitoids and the emergence of the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…Several bioinsecticides have been tested on D. suzukii and T. absoluta, with spinosad, azadirachtin, and pyrethrins among the most common active ingredients targeting both insect pests. While commonly used bioinsecticides mainly target D. suzukii adults, they can also affect pest immature stages and/or natural enemies because of their broad-spectrum action [10,27,28]. Avermectins, essential oils, and microbial-based biopesticides are additional tools for managing T. absoluta in organic contexts [18,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the non-target impact of insecticides with different origins and Mechanisms of Action (MoA) towards key natural enemies of D. suzukii [28,36] and T. absoluta [37][38][39]. However, the potential compatibility of biopesticides with Ganaspis kimorum Buffington (Hymenoptera: Figitidae) and Necremnus tutae Ribes & Bernardo (Hymenoptera: Eulophidae), which are among the most important larval parasitoids of D. suzukii and T. absoluta, respectively, is still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Spotted wing Drosophila, D. suzukii, is one of the most destructive polyphagous pests in soft-skinned fruits, including blueberries, strawberries, cherries, and raspberries (Karageorgi et al, 2017;Lisi et al, 2023;McIntosh et al, 2022;Vijayan et al, 2022). It is endemic to East Asia, and currently widespread throughout the Americas and Europe as an invasive species that is notoriously di cult to control (Kwadha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%